Testing Homes for Potential Sources of Lead Exposure as a High‐School Science Project - Evan M. Sefchick (American Geophysical Union (AGU), 2021)
Abstract High‐school students tested soil, paint, and water for lead (Pb) in a total of 80 houses in their town of Pelham, New York, where blood‐Pb data indicate relatively high levels of child exposure. All the samples were tested in the laboratory using established procedures but this was preceded by testing of soil and paint in the field with a kit by the students. The total Pb concentration in 32 of the 159 soil samples that were collected exceeded 400 ppm, the EPA standard for bare soil in residential areas where children play. Only 4 of the 118 tap water samples that were collected contained over 15 ppb Pb, with the data showing that flushing for 2 min clearly lowered Pb concentration further across the board. The highest risk of child exposure may be posed by old Pb‐based paint, however, which was detected in 9 of the 48 samples that were tested. Residents were also the least willing to let the students test or sample their paint. High‐school students could help reduce exposure in the many towns where child blood‐Pb levels remain high today by identifying sources and, while doing so, learn about environmental science and measurement from this hands‐on experience.